Analisis Dampak Sosial Ekonomi Relokasi Pedagang Kaki Lima (PKL) terhadap Masyarakat (Studi PKL di Gelanggang Olah Raga (GOR) Kabupaten Sidoarjo) - Mochammad Hatta Karuniawan; Ardi Perdana Sukma; Efandi Dwi Kurniawan (Universitas Muhammadiyah Sidoarjo, 2015)
The aim of this research was to explain the effects after relocation of street vendors in the Sports Arena, Sidoarjo Regency. This research used descriptive-qualitative analysis. The technique of this research is conducted by observation and interviews in depth to compare empirical reality with the theory related to the socio-economic impacts. Based on the results of the study, it is indicated that there are positive and negative impacts in relocating of street vendors. The positive impact of relocation namely economic conditions street vendors (PKL) is supported by many buyers that is coming in the location of trade moved. While the negative impact of relocation, among others, the first Sports Arena became irregular that interfere its function as a sport facilities. Second was the impact on the environmental factors that were not clean and looks dirty, and the third is reduced guarantees the safety of street vendors.